2021
DOI: 10.3389/fpls.2021.643585
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethylene Signaling in the Crosstalk Between Fe, S, and P Deficiency Responses in Arabidopsis thaliana

Abstract: To cope with P, S, or Fe deficiency, dicot plants, like Arabidopsis, develop several responses (mainly in their roots) aimed to facilitate the mobilization and uptake of the deficient nutrient. Within these responses are the modification of root morphology, an increased number of transporters, augmented synthesis-release of nutrient solubilizing compounds and the enhancement of some enzymatic activities, like ferric reductase activity (FRA) or phosphatase activity (PA). Once a nutrient has been acquired in eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 82 publications
0
29
0
Order By: Relevance
“…Recently, Garcia et al (2021) reported the involvement of phytohormone ethylene (ET) in the regulation of crosstalk between P, S, or Fe deficiency. Some of the key elements of the ET transduction pathway (CTR1, EIN2, and EIN3/EIL1) were reported to play roles in nutrient deficiency responses.…”
Section: Interaction Between P and S Homeostasis In Plantsmentioning
confidence: 99%
“…Recently, Garcia et al (2021) reported the involvement of phytohormone ethylene (ET) in the regulation of crosstalk between P, S, or Fe deficiency. Some of the key elements of the ET transduction pathway (CTR1, EIN2, and EIN3/EIL1) were reported to play roles in nutrient deficiency responses.…”
Section: Interaction Between P and S Homeostasis In Plantsmentioning
confidence: 99%
“…Several responses to both deficiencies are similar, like rhizosphere acidification, enhanced synthesis of organic acids and coumarins, and development of subapical root hairs and proteoid roots. Furthermore, both kinds of responses share common regulators, such as ET and nitric oxide (NO), which increase their production in Fe-deficient roots as well as in P-deficient roots [ 33 , 81 , 82 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Role Of Et and No In The Regulation Of Fe And P Deficiency Responses Similarities And Differencesmentioning
confidence: 99%
“…YID1 encodes the Arabidopsis Mediator complex subunit MED16, which interacts with MED25 and subsequently with EIN3/EIL1 to regulate FIT transcription [ 41 ]. Very recently, García et al [ 98 ] found that several Fe and P deficiency responses can also be induced in the Arabidopsis ethylene insensitive ein3eil1 mutant, which suggests the existence of additional EIN3/EIL1-independent alternate routes for the activation of such responses. However, some of these Fe and P deficiency responses are impaired in Arabidopsis ethylene insensitive ein2 mutants, which suggests the participation of the EIN2 protein, a critical component of the canonical ethylene signaling pathway, in such a regulation [ 128 ].…”
Section: Mechanisms For the Induction Of Fe- And P-related Genes By Et And Nomentioning
confidence: 99%
“…Beneficial microbes-induced ISR overlaps with plant Fe deficiency response [ 56 ]. Fe deficiency response can result from the Pi deficiency-induced JA pathway through signal crosstalk [ 46 , 57 ]. It can also result from ethylene (ET) reduction that can be accomplished by the ACC deaminase-producing bacteria such as SSG [ 14 , 30 ].…”
Section: Discussionmentioning
confidence: 99%